2013
DOI: 10.1038/bjc.2013.587
|View full text |Cite
|
Sign up to set email alerts
|

Aromatase inhibitor-induced modulation of breast density: clinical and genetic effects

Abstract: Background:Change in breast density may predict outcome of women receiving adjuvant hormone therapy for breast cancer. We performed a prospective clinical trial to evaluate the impact of inherited variants in genes involved in oestrogen metabolism and signalling on change in mammographic percent density (MPD) with aromatase inhibitor (AI) therapy.Methods:Postmenopausal women with breast cancer who were initiating adjuvant AI therapy were enrolled onto a multicentre, randomised clinical trial of exemestane vs l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 46 publications
1
22
0
Order By: Relevance
“…Many of the studies which have no change in MD limited AI therapy to 12 months (10-12, 35). However, our study along with at least one other study (13) which evaluated AI therapy for 24 months did note a significant decrease in MD at the 24 month evaluation point. Unfortunately, our study was powered to evaluate MD at 12 months and not at 24 months.…”
Section: Discussionsupporting
confidence: 46%
See 2 more Smart Citations
“…Many of the studies which have no change in MD limited AI therapy to 12 months (10-12, 35). However, our study along with at least one other study (13) which evaluated AI therapy for 24 months did note a significant decrease in MD at the 24 month evaluation point. Unfortunately, our study was powered to evaluate MD at 12 months and not at 24 months.…”
Section: Discussionsupporting
confidence: 46%
“…While the strength of our conclusions is limited by the lack of a control arm, comparable control groups of postmenopausal women have a MD change of +0.58 to −0.8 at one year follow-up (10-12) suggesting that the observed decline of 2.4% at 1 year and 4.1% at 2 years in our study may be significant. Henry et al noted (13) a similar decline of 5.8% at 2 years in the contralateral breast in women with early breast cancer on exemestane or letrozole. A small pilot study by Smith et al (32) found that letrozole use was associated with a reduction in MD over 12 months in 11 of their 16 patients.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…97 SERMs also decrease insulin-like growth factor (IGF)-1 levels and increase IGF binding protein (IGFBP) and sex hormone binding-globulin. 8,9,15 Other substances (AIs) inhibit the production of estrogen by aromatase. 15,56 Evidence shows that TAM mediates BD reduction in both premenopausal and postmenopausal women, but no concrete evidence exists for BD reduction with RLX, tibolone, letrozole, anastrozole, or exemestane ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…8,9,15 Other substances (AIs) inhibit the production of estrogen by aromatase. 15,56 Evidence shows that TAM mediates BD reduction in both premenopausal and postmenopausal women, but no concrete evidence exists for BD reduction with RLX, tibolone, letrozole, anastrozole, or exemestane ( Table 2). The BD reduction in TAM studies might be explained by the prevalence of premenopausal women as shown by the stronger BD decreases in premenopausal women.…”
Section: Discussionmentioning
confidence: 99%